Stabilization of chromium(VI) by hydroxysulfate green rust in chromium(VI)-contaminated soils - ALIDOKHT, Leila; OUSTAN, Shahin; KHATAEE, Alireza; NEYSHABURI, Mohammad R.; REYHANITABAR, Adel (Pedosphere, 2021)
Chromium (Cr)-contaminated soils pose a great environmental risk, with high solubility and persistent leaching of Cr(VI). In this study, hydroxysulfate green rust (GRSO4), with the general formula Fe(II)4Fe(III)2(OH)12SO4·8H2O, was evaluated for its efficiency in Cr(VI) stabilization via Cr(VI) reduction to Cr(III) in four representative Cr(VI)-spiked soils. The initial concentrations of phosphate buffer-extractable Cr(VI) (Cr(VI)b) in soils 1, 2, 3, and 4 were 382.4, 575.9, 551.3, and 483.7 mg kg–1, respectively. Reduction of Cr(VI) to Cr(III) by structural Fe(II) (Fe(II)s) in GRSO4 in all studied soils was fast, wherein the application of GRSO4 markedly decreased the amount of Cr(VI)b at the Cr(VI)b/Fe(II)s stoichiometric mole ratio of 0.33. The kinetics of Cr(VI) reduction by GRSO4 could not be determined as this reaction coincided with the release of Cr(VI) from soil during the experiment. The concentration of Cr(VI)b decreased, as the Cr(VI)b/Fe(II)s ratio decreased from 0.46 to 0.20, generally to below 10 mg kg–1. Back-transformation of the generated Cr(III) was examined in the presence of manganese oxide birnessite at the birnessite/initial Cr(III) mole ratio of 4.5. The results of batch tests showed that only 5.2% of the initial Cr(III) was converted to Cr(VI) after two months, while under field capacity moisture conditions, less than 0.05% of the initial Cr(III) was oxidized to Cr(VI) after six months. The results illustrated that remediation of Cr(VI)-contaminated soils would be fast, successful, and irreversible with an appropriate quantity of fresh GRSO4.